PUFA n-3, PUFA n-6 and non-alcoholic fatty liver disease: pathogenesis and therapeutical approach - Laurino, Carmen; Palmieri, Beniamino (Progress in Nutrition, 2015)
Fatty acids are structural molecules of vegetable and animal lipids. Among this class our attention has been focused upon, omega 3 polyunsatured fatty acids (PUFA n-3) (Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) and omega 6 polyunsatured fatty acids (PUFA n-6). They are synthetized by human cells only in small amounts, and an adequate nutritional intake is required. Fatty fishes, fish and vegetable oils are the most important sources of these compounds, but also some seaweeds supply PUFA n-3. Omega 3  have recently been  addressed  to prevention and management of and non-alcoholic fatty liver disease (NAFLD),  specifically induced  to obesity, insulin resistance, and high  sugar and  high saturated fatty acids diets. The current review analyzes  an update of clinical studies of PUFA n-3and  PUFA n-6 administration in NAFLD patients. In comparison we have reviewed the main NAFLD management behavioral strategies such as body weight reduction, diet modifications, supplementation and drugs therapy .